Urgensi Pembelajaran Kaligrafi Metode Hamidi di Era Society 5.0 dalam Melestarikan Seni Kebudayaan Islam - Bukhori Ibnu Athoillah; Emi Lilawati; Abdur Ro'uf Hasbullah (JOM, 2024)
The rapid development of technology leading to the emergence of the Society 5.0 era, many challenges must be faced, including in the field of calligraphy. Therefore, it is important to have a calligraphy learning model that can equip students to face various challenges in line with the times. This research aims to examine how the Hamidi method of calligraphy learning is implemented at the Denanyar Jombang Qur'anic Calligraphy School (SAKAL) and its urgency in the Society 5.0 era in preserving Islamic cultural arts. This study uses a qualitative method with a descriptive approach. Data were collected through observation, interviews, and documentation. The results showed that the Hamidi method of learning calligraphy at SAKAL is structured and systematic, offering various applications. This greatly supports efficiency in learning and provides multiple options for practice. The emphasis on holistic research and learning, as well as character education, is highly relevant in preparing a creative, innovative, and competitive generation, while also nurturing individuals with strong character traits suited for the Society 5.0 era. Furthermore, with the concept of sanad, which serves as a trusted and authoritative source and is a distinctive feature of the Islamic scientific tradition, learning calligraphy through the Hamidi method remains rooted in tradition. This contributes significantly to preserving Islamic cultural arts in the Society 5.0 era.